Pengembangan Modul IPA Braille Berbasis Integrasi Islam dan Sains - Mukaromah, Siti Maulidatul (PLD UIN Sunan Kalijaga, 2018)
This study aims at developing a Braille module based on the integration of Islam and science in elementary school. The study uses the rating scale sheet as the instrument. Experts are requested to asses the learning modules. In addition, three students with disabilities are asked to give their response to the learning module. The quantitative data of its feasibility are then converted into qualitative data. The quantitative data were analysed by each aspect of the assessment. The final score obtained is transformed into qualitative product feasibility. The result of this research are (1) the compilation of the module; (2) validation results from experts and reviewers are very good with an average of 4.40 (meaning that the module is adequate as a reference for learning). (3) Based on the response of three students, all of them responded positively with a mean score of 9.[Penelitian ini bertujuan untuk mengembangkan modul IPA Braille berbasis integrasi Islam dan sains untuk peserta didik tunanetra MI/SD kelas IV. Penelitian dan pengembangan ini menggunakan model pengembangan 4D yang terdiri dari empat tahap yaitu define, design, development, dan disseminate; tetapi tanpa tahap disseminasi. Instrumen yang digunakan yaitu lembar skala penilaian. Modul pembelajaran dinilai oleh ahli materi, ahli integrasi Islam dan sains, ahli media, ahli PLB (Pendidikan Luar Biasa) dan reviewer. Modul pembelajaran juga direspon oleh 3 peserta didik tunanetra kelas IV. Penelitian ini meghasilkan: (1) Modul IPA Braille berbasis integrasi Islam dan sains untuk peserta didik tunanetra MI/SD kelas IV. (2) Hasil validasi pra ahli menunjukan sangat baik (SB) dengan skor rata-rata 4.4; dan (3) Tiga peserta didik tunanetra kelas IV, semuanya merespon positif, dengan skor rata-rata 9.]